Leveraging communities of practice for strategic advantage - Saint-Onge, Hubert (Butterworth-Heinemann, 2003)
How can you build a successful community of practice that is integrally linked to your company's strategic vision? Learn from the first-hand experience of Hubert Saint-Onge, recognized by Fortune magazine as a leader in the field of knowledge capital, and co-author Debra Wallace, the people responsible for a recent project to establish a community of practice for independent agents at Clarica Life Insurance Company- voted one of the most admired knowledge enterprises in the world by practitioners and researchers. 'Leveraging Communities of Practice for Strategic Advantage' combines theory and practice to outline a model for developing successful communities of practice and proposes a direction for establishing communities of practice as an integral part of the organizational structure. Saint-Onge and Wallace relate what worked, what didn't, and why as they tell the story from inception through implementation to assessment. Whether you're developing communities of practice or want to learn how to leverage existing communities for strategic gain, this book provides you with everything you need to launch successful communities of practice in your organization. * Hubert Saint-Onge has been recognized by Fortune magazine as a leader in the area of leveraging knowledge capital * Clarica has been voted one of the most admired knowledge enterprises in the world by practitioners and researchers * Combines theory and practice to outline a model for developing successful communities of practice.